An overview of structured illumination microscopy: recent advances and perspectives. (19th November 2021) - Samanta, Krishnendu; Joseph, Joby
Abstract: Structured illumination microscopy (SIM) is one of the most significant widefield super-resolution optical imaging techniques. The conventional SIM utilizes a sinusoidal structured pattern to excite the fluorescent sample; which eventually down-modulates higher spatial frequency sample information within the diffraction-limited passband of the microscopy system and provides around two-fold resolution enhancement over diffraction limit after suitable computational post-processing. Here we provide an overview of the basic principle, image reconstruction, technical development of the SIM technique. Nonetheless, in order to push the SIM resolution further towards the extreme nanoscale dimensions, several different approaches are launched apart from the conventional SIM. Among the various SIM methods, some of the important techniques e.g. TIRF, non-linear, plasmonic, speckle SIM etc are discussed elaborately. Moreover, we highlight different implementations of SIM in various other imaging modalities to enhance their imaging performances with augmented capabilities. Finally, some future outlooks are mentioned which might develop fruitfully and pave the way for new discoveries in near future.